2022
DOI: 10.1128/spectrum.00872-22
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Sugar Transporter CRT1 Reveals Differential Roles of Its C-Terminal Region in Sugar Transport and Cellulase Induction in Trichoderma reesei

Abstract: The lignocellulose-degrading fungus T. reesei has been widely used in industrial cellulases production. Understanding the precise cellulase gene regulatory network is critical for its genetic engineering to enhance the mass production of cellulases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…These experiments have helped to separate nutrient sensing from substrate transport, and indicate that MtLat-1 protein serves as a transceptor, which might sense and transduce molecular signal of l -arabinose, one of the end products of hemicellulose degradation, to repress the induction of hemicellulase genes. The role of transceptor in the induction of genes involved in plant biomass degradation has also been demonstrated for CDT-1/2 in N. crassa and Crt1 in T. reesei [ 9 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These experiments have helped to separate nutrient sensing from substrate transport, and indicate that MtLat-1 protein serves as a transceptor, which might sense and transduce molecular signal of l -arabinose, one of the end products of hemicellulose degradation, to repress the induction of hemicellulase genes. The role of transceptor in the induction of genes involved in plant biomass degradation has also been demonstrated for CDT-1/2 in N. crassa and Crt1 in T. reesei [ 9 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the deletion of these factors was reported to cause loss or reduction of cellulase expression 38 40 , 45 . These factors were also affected by enhanced expression of XYR1 and ACE3 (for example, crt1 is regulated by ACE3 38 , 47 ). This suggested that the effect of co-expression of XYR1 V821F with these factors may not have occurred because sufficient amounts of these factors were already upregulated by the constitutive expression of mutated XYR1 V821F and subsequent upregulation of ACE3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the deletion of these factors was reported to cause loss or reduction of cellulase expression [38][39][40]45 . These factors were also affected by enhanced expression of XYR1 and ACE3 (for example, crt1 is regulated by ACE3 38,47 ). This suggested that the effect of co-expression www.nature.com/scientificreports/ production (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations